INTERAKSI KEBERADAAN TUNGAU SARCOPTES SCABIEI TERHADAP KEJADIAN PENYAKIT SKABIES - Riyana Husna; Reza Olyverdi; Putri Rahmadani; Cici Aprilliani (LLDIKTI Wilayah X, 2023)
Scabies was a skin disease caused by infestation and sensitization by the mite Sarcoptes scabiei. This study aims to identify and analyze the presence of the scabies mite on the incidence of scabies in the community. This study used an observational method with a cross-sectional approach. The population in this study is the people who are in Lubuk Begalung District, Padang City. With a sample of 112 samples. Data collection through interviews, observation and examination of dust on the bed, carpet and mattress base. Data analysis in this study used the Chi-square test. The results showed that 34.8% of the respondents who suffered from scabies in Lubuk Begalung District Variables that have a relationship with the incidence of scabies in the community are: gender (p=0.013, PR=2.128, 95% CI=1.180-3.839), presence of scabies mites (p=0.001, PR=3.209, 95% CI=1.859-5.541 ). The conclusion is that scabies mites are found in respondents who suffer from scabies in the bedroom, namely on mattress pads, prayer rugs and carpets.